50% ethanol extract cytotoxic test of temulawak on MCF-7 breast cancer cells - Anindita, Kintan; Syamsudin, Syamsudin; Nuralih, Nuralih; Djamil, Ratna; Swandiny, Greesty Finotory (International Journal Labs, 2023)
According to WHO, the number of breast cancer sufferers always increases from year to year. One of the medicinal plants used is temulawak. The levels of active compounds in plants can differ depending on several factors, one of which is the planting location, therefore research was conducted on the cytotoxicity of 50% ethanol extract of temulawak rhizomes from 5 regions on MCF-7 breast cancer cells in vitro using the MTT-Assay method. Temulawak used in this research comes from 5 regions in Indonesia, namely Tembalang, Wonogiri, Jambi, Sumba and Sukabumi. Cytotoxic testing of 50% ethanol extract of temulawak rhizomes used 6 concentrations, namely 500; 250; 125; 62.5; 31.25; and 15,625 ppm. The IC50 value obtained from 50% ethanol extract of temulawak rhizomes from Tembalang, Wonogiri, Jambi, Sumba and Sukabumi at MCF-7 was 109; 550.9; 622.3; 341.6; and 116.5 ppm. The results of the cytotoxic test showed that the 50% ethanol extract of temulawak rhizomes from Tembalang obtained the best IC50 value compared to temulawak rhizome extracts from other areas.